Investigation of the frequency dispersion of the complex permittivity of lithium-iron spinel doped with La,Y - Vakalyuk, A.V.; Vakalyuk, V.M.; Voitkiv, H.V.; Gasiuk, I.M. (Physics and Chemistry of Solid State, 2024)
The temperature-frequency dependences of the complex dielectric permittivity of Li2Fe2.5-xMexO4 (Ме = La; Y, x = 0.01; 0.03; 0.05) spinels, synthesized by the «sol-gel» autocombustion technology, were obtained by the method of impedance spectroscopy, in temperature range 298-473K. Their analysis indicates the presence of a fractal structure in the studied samples, the influence of which is manifested in the entire studied temperature interval. To study the electric polarization phenomenon associated with this structure, Josher's generalized law has been used.